2014
DOI: 10.1021/la500589f
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Self-Assembled Fmoc-Diphenylalanine Molecular Gels

Abstract: We explore the phase diagram and mechanical properties of molecular gels produced from mixing water with a dimethyl sulfoxide (DMSO) solution of the aromatic dipeptide derivative fluorenylmethoxycarbonyl-diphenylalanine (Fmoc-FF). Highly soluble in DMSO, Fmoc-FF assembles into fibrous networks that form gels upon addition of water. At high water concentrations, rigid gels can be formed at Fmoc-FF concentrations as low as 0.01 wt %. The conditions are established defining the Fmoc-FF and water concentrations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 41 publications
5
86
3
Order By: Relevance
“…Rheological studies showed that G’ values observed for the SA5N hydrogels are dependent of peptide concentration and are an order of magnitude higher compared to those reported in the literature for other small peptides . The elastic storage moduli recorded for the H1, H2, H3 hydrogels are closer to those observed for Fmoc‐dipeptide based hydrogels, where the main driving forces for self‐assembly are based on an extensive π‐ π stacking of the aromatic fluorenyl moiety . These data let us to infer that SA5N peptide hydrogels have a more complex network structure with higher numbers of fiber‐fiber interactions due to the presence of three aromatic phenyl groups in the side chains of the self‐assembling peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Rheological studies showed that G’ values observed for the SA5N hydrogels are dependent of peptide concentration and are an order of magnitude higher compared to those reported in the literature for other small peptides . The elastic storage moduli recorded for the H1, H2, H3 hydrogels are closer to those observed for Fmoc‐dipeptide based hydrogels, where the main driving forces for self‐assembly are based on an extensive π‐ π stacking of the aromatic fluorenyl moiety . These data let us to infer that SA5N peptide hydrogels have a more complex network structure with higher numbers of fiber‐fiber interactions due to the presence of three aromatic phenyl groups in the side chains of the self‐assembling peptide.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest the possibility to design novel peptide based materials with enhanced properties. By this evidence, many structural analogues of diphenylalanine (like WF, LF, FFF, FFFF, di‐3,4‐dihydroxyphenylalanine and Fmoc‐FF) and their PEGylated‐polymer conjugates have been reported …”
Section: Introductionmentioning
confidence: 86%
“…The high cytocompatibility detectedi nv itro can be probably attributed to the hydrogel preparation method that, contrarily to others peptideh ydrogels, does not require the employment of any organic solvents (like DMSO, HFIP,orM eOH). [36]…”
Section: In Vitro Biocompatibilityprofiles Of Peg 8 -(Fy)3 Gelmentioning
confidence: 99%